Antibacterial Test of Endophytic Bacteria Isolated from Jawer Kotok (Coleus scutellarioides L. Benth) Against Bacillus cereus and Salmonella enteritidis - Kusumawati, Dwi Endah; Bintang, Maria (Current Biochemistry, 2023)
The use of synthetic antibiotics in small doses and long term against pathogenic bacteria can cause negative effects, such as resistance of pathogens and killing of good bacteria. We needs an innovation to substitute the use of synthetic antibiotics with natural antimicrobial compounds. Jawer kotok (Coleus scutellarioides L. Benth) has been used as medicinal plant and shown to be efficacious as antimicrobial because it contains flavonoids, tannins, alkaloids and saponins. Endophytic bacteria are symbiotic microorganisms that live in healthy plant tissue without harming to the host plant and may produce natural antimicrobial compounds which similar to the host plant. The aim of this study are to isolating endophytic bacteria from jawer kotok and screening their antibacterial activity against two pathogenic bacteria, namely Bacillus cereus and Salmonella enteritidis. A total of 22 bacterial isolates were obtained from C scutellarioides [L.] Benth. Based on antibacterial activity test, nine isolates shown antibacterial activity against B. cereus and S.enteritidis. BJ7 is the most potential isolate because it shown the biggest inhibition. It great possible that endophytic bacteria from jawer kotok may synthesize the same antimicrobial compounds like their host plant.